Dysfunctional Freezing Responses to Approaching Stimuli in Persons with a Looming Cognitive Style for Physical Threats - Riskind, John H.; Sagliano, Laura; Trojano, Luigi; Conson, Massimiliano (Frontiers in Psychology, 2016)
Immobilizing freezing responses are associated with anxiety and may be etiologically related to several anxiety disorders. Although recent studies have sought to investigate the underlying mechanisms in freezing responses that are so problematic in many forms of anxiety, cognitive factors related to anxiety have not been investigated. This study was designed to investigate the potential moderating role of a well-documented cognitive vulnerability to anxiety, the Looming Cognitive Style (i.e., LCS; Riskind et al., 2000), which assesses the extent to which individuals tend to routinely interpret ambiguous threats (e.g., physical or social threats) in a biased manner as approaching. We assessed participants’ Reaction Times (RTs) when they made judgments about images of animals that differed in threat valence (threat or neutral) and motion direction (approach or recede). As expected, LCS for concerns about the approach of physical dangers appeared to moderate freeze reactions. Individuals who were high on this LCS factor tended to generally exhibit a freeze-response (slower RTs) and this was independent of the threat valence or motion direction of the animals. These general freezing reactions were in stark contrast to those of individuals who were low on the LCS factor for concerns about the approach of physical dangers. These participants tended to exhibit more selective and functional freezing responses that occurred only to threatening animals with approach motion; they did not exhibit freezing to neutral stimuli or any stimuli with receding motion. These findings did not appear to be explicable by a general slowing of RTs for the participants with high LCS. Moreover, the LCS factor for concerns about social threats (such as rejection or embarrassment) was not related to differences in freezing; there was also no additional relationship of freezing to behavioral inhibition scores on the Behavioral Inhibition System and the Behavioral Activation System Scales (BIS/BAS). It may prove fruitful to further explore cognitive factors related to anxiety to develop a more comprehensive understanding of how these factors are associated with anxiety-related freezing responses.